2002
DOI: 10.1046/j.1365-2249.2002.01805.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of muco-cutaneous signs of toxic shock syndrome when T cells are absent:S. aureusshock in immunodeficient adults with multiple myeloma

Abstract: Staphylococcal toxic shock syndrome (TSS) is an acute life threatening disease. The diagnosis can be made clinically based on diagnostic criteria. The clinical manifestations are caused in large part by there lease of high levels of T-cell-derived cytokines as a result of potent toxins, also called superantigens (SAg), produced by Staphylococcus aureus, but it is not clear which clinical symptoms/signs are strictly T-cell dependent. Here, we report on three adults with multiple myeloma (MM) presenting with S.a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…However, cases of TSS without cutaneomucous involvement have already been reported and were confirmed by the proliferation of specific Vb-restricted T cells in response to the superantigen [9]. Moreover, desquamation usually occurs 1-2 weeks after onset of TSS, and the patients we describe died 4 and 7 days after the onset of infection [6].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, cases of TSS without cutaneomucous involvement have already been reported and were confirmed by the proliferation of specific Vb-restricted T cells in response to the superantigen [9]. Moreover, desquamation usually occurs 1-2 weeks after onset of TSS, and the patients we describe died 4 and 7 days after the onset of infection [6].…”
Section: Discussionsupporting
confidence: 75%
“…These cytokines and, especially, TNF-a cause a capillary link syndrome, which generally leads to toxic shock syndrome (TSS) [5]. TSS usually occurs when large amounts of staphylococcal superantigenic toxins are secreted into the circulation, even in immunocompromised patients [6]. Nonmenstrual TSS is now more common than menstrual TSS [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight were obtained at the height of a TSS epidemic in 1983 [3]; 4 were recent isolates; 6 were from cases of menstrual TSS; 6 were from cases of nonmenstrual TSS; and 2 were from immunodeficient patients with atypical presentation of TSS [4]. There was no obvious correlation with these clinical groups in terms of SAG genes found by PCR.…”
Section: Resultsmentioning
confidence: 96%
“…Although early epidemiologic reports note a few cases lacking rashes [4], Van Lierde et al [10] and Matsuda et al [11] published full clinical descriptions of individual cases. Kamel et al concluded that the absence of rash in three TSS patients, who underwent chemotherapy for multiple myeloma, reflected T cell deficiency [12]. …”
Section: Discussionmentioning
confidence: 99%